The Influence Of Financial Literacy And Financial Attitudes On Student Saving Behaviour Mediated By Pocket Money Variables - Aidil Putra Pratama; Herman Paleni; Muhamad Effendi (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the effects of financial literacy and financial attitude on students' saving behavior, as well as the role of pocket money as a mediator. A quantitative approach with a descriptive-causal design was employed on 90 students of the Management Study Program, Bina Insan University, class of 2024/2025, using simple random sampling. The research instruments were tested for validity and reliability, while data analysis was conducted using SEM-PLS to assess direct, indirect, and mediation effects. The results indicate that financial literacy has a positive and significant effect on saving behavior (coefficient = 0.268; T-statistic = 4.186; P < 0.001), as does financial attitude (coefficient = 0.319; T-statistic = 4.410; P < 0.001). Mediation analysis reveals that pocket money does not significantly mediate the effect of financial literacy but serves as a partial mediator between financial attitude and saving behavior (coefficient = 0.284; T-statistic = 5.473; P < 0.001). The findings confirm that financial literacy and financial attitude are primary factors shaping students’ saving behavior, while pocket money reinforces the influence of attitude when adequately provided. Practically, these results underscore the importance of integrated financial education interventions, encompassing literacy enhancement, positive financial attitude development, and effective pocket money management. This study provides empirical evidence to inform financial education policies and strategies aimed at fostering sustainable saving behavior among university students.